Cobalt (II)-Mediated Molecularly Imprinted Polymer as a Monolithic Stationary Phase for Separation of Racemic Citronellal by Liquid Chromatography. (28th February 2022) - Amalia, Suci; Rafika, Nilna Assasiatur; Hardiyanti, Shova Audinia; Ashari, Adi Dwi; Khabibi, Bhisma Wildan; Iftitah, Elvina Dhiaul; Warsito, Warsito; Hasanah, Aliya Nur; Sabarudin, Akhmad
Abstract : A metal-mediated molecularly imprinted polymer (MMIP) monolithic column was prepared as the stationary phase for high-performance liquid chromatography (HPLC) and applied to the enantiomeric separation of rac -citronellal. MMIP column was prepared through in situ copolymerizations with the ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate/[BMIM][BF4 ] as the primary pore-forming agent and cobalt(II) acetate as the metal pivot. Interactions between polymer components in the synthesized monolith were assessed by FTIR to identify the functional groups. The monolith morphology was characterized with SEM, and the template removal was detected by UV Spectrophotometry at 253 nm. In this study, (R)-(+)-citronellal was used as a template, whereas 4-vinylpyridine (4-VP) was employed as the functional monomer with two monomer crosslinkers, trimethylolpropane trimethacrylate (TRIM), and ethylene glycol dimethacrylate (EDMA). The ternary mixture of porogenic solvent consisted of [BMIM][BF4 ], dimethylformamide (DMF), and dimethyl sulfoxide (DMSO) with the applied ratio of 1 : 1:1 (v/v) and 10 : 1:5 (v/v) for the preparation of MMIP using TRIM and EDMA crosslinkers, respectively. Co(II) ion was added to the porogenic solvent before being mixed with the functional monomer and the crosslinker mixtures. Separating the rac -citronellal was achieved on the synthesized MMIP, showing better selectivity than the monolithic metal-mediated nonimprinted polymer (MNIP), nonimprinted polymer (NIP), and molecularly imprinted polymer (MIP).